Gamma-linolenic acid ameliorates Aβ-induced neuroinflammation through NF-κB and MAPK signalling pathways. (March 2018) - Youn, Kumju; Lee, Seonah; Jun, Mira
Graphical abstract: Highlights: Anti-inflammatory activities and their molecular mechanism of GLA were studied. GLA inhibited Aβ25–35 -induced intracellular ROS and apoptosis. GLA blocked activation of NF-κB translocation induced by Aβ25–35 . GLA suppressed Aβ25–35 -stimulated ERK and JNK phosphorylation. Abstract: Beta-amyloid (Aβ) are known to form senile plaques causing neuroinflammation, which was accepted as the major pathological mechanism in Alzheimer's disease (AD). To elucidate the molecular mechanism of gamma-linolenic acid (GLA) on neuroprotective actions in inflammation, the effect of GLA on Aβ25–35 -stimulated in PC12 cells was investigated. Pre-treatment of GLA significantly decreased Aβ25–35 -mediated cytotoxicity through the reduction of ROS and downregulation of caspase-3, thereby attenuating apoptotic morphological alteration. GLA inhibited the production of proinflammatory cytokines including TNF-α and PGE2, and further blocked NF-κB subunit p65 activation by suppressing IκB-α degradation. Mechanistic studies revealed that the inhibitory effect of GLA was accompanied by reducing expression of ERK1/2 and JNK activity but not by p38 MAPK. In conclusion, given that GLA prevents the Aβ25–35 damage via NF-κB signaling pathway, all of which may provide an exciting view of the potential application of GLA as a future research for AD.